Preparation method and application of nickel-titanium composite catalyst

By preparing a nickel-titanium composite catalyst, the metal Ni/TiO2 interaction is regulated by the TiO2 support particle size, the photogenerated charge separation efficiency is improved, and the demand for high temperature and high pressure during CO2 conversion in the prior art is solved, and the efficient catalyzing of CO2 under mild conditions is achieved Hydrogenation reaction and adjust product selectivity.

CN119488913APending Publication Date: 2025-02-21INST OF URBAN ENVIRONMENT CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310986096.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When converting CO2 into value-added products or solar fuels, the prior art faces the demand for high temperature and high pressure, with huge energy consumption and insufficient selectivity and stability of the catalyst.

Method used

Using a nickel-titanium composite catalyst, a catalyst with high light absorption and photothermal conversion ability was prepared by calculating TiO2 in the presence of a reducing gas and mixing it with a Ni precursor solution. The TiO2 support particle size of the catalyst is adjustable, adjusting the interaction between metal Ni/TiO2, improving the photogenerated charge separation efficiency, and thus adjusting the selectivity of CO2 hydrogenation reaction products.

Benefits of technology

It has achieved efficient catalytic CO2 hydrogenation reaction under mild conditions, adjusted product selectivity, and the catalyst can be efficiently converted without an external heating device, with good stability and industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488913A_ABST
    Figure CN119488913A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nickel-titanium composite catalyst, and the preparation method of the nickel-titanium composite catalyst comprises the following steps: (1) roasting TiO2 in the presence of a reducing gas to obtain an intermediate; and (2) mixing and heating the intermediate obtained in the step (1) and a Ni precursor solution, and roasting in the presence of reducing gas to prepare the nickel-titanium composite catalyst. The preparation method of the catalyst provided by the invention has the advantages of easily available raw materials, simple process and easiness in industrialization. By changing the particle size of the TiO2 carrier, the interaction between metal Ni / TiO2 can be effectively adjusted, then the Ni / TiO2 photo-generated charge separation efficiency is adjusted, and finally the selectivity of a carbon dioxide hydrogenation reaction product is adjusted. The catalyst provided by the invention can realize photothermal conversion without an external heating device, and the nickel-titanium composite catalyst can realize strong light absorption under a full spectrum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and relates to a preparation method of a nickel-titanium composite catalyst and application thereof. Background Art

[0002] Over the past two centuries, population growth, urbanization, modernization and industrialization, socio-economic and scientific development have increased global energy demand. Crude oil, coal and natural gas, known as fossil fuels, are the main sources of primary energy in the world (accounting for 85%). This high dependence on fossil fuels is accompanied by large amounts of anthropogenic greenhouse gas emissions into the atmosphere, mainly in the form of carbon dioxide (CO 2 ) in the form of carbon dioxide. It causes global warming, climate change, and various other related environmental problems, including acid rain, extreme weather events, unbalanced food distribution, malnutrition, and large-scale migration of birds and animals. According to recent scientific reports, from 1750 to 2011, the amount of CO in the atmosphere 2 increased by 40%, and atmospheric CO 2 It can last from 100 to 10,000 years. Considering the CO 2 The harmfulness of the increased concentration of CO 2 Its removal or transformation is imminent.

[0003] CO 2 Conversion into value-added products or solar fuels is a strategy that kills two birds with one stone, however, due to the 2 The kinetic inertness and high thermodynamic energy barrier of CO 2 There are still great difficulties and challenges in the activation and high-selective conversion of CO into target products. 2 The conversion is effective, but requires high temperatures (150-500°C) and pressures, and consumes a lot of energy. Using solar energy as a driving force for photothermal reduction of carbon dioxide is an important and attractive research area. Photothermal catalysis often has higher catalytic activity and milder conditions than thermal catalysis through photothermal conversion and photoinduced electrons to promote the reaction. In addition, the photoexcited electrons involved in the catalysis may also change the reaction pathway and improve the selectivity of specific products. Supported metal catalysts are often used to catalyze CO 2 The construction strategy of hydrogenation catalysts is usually to load precious metals such as Pt, Ru, or Ni, Co, Cu, etc. with strong hydrogen dissociation ability on a carrier (such as TiO 2 、CeO 2 ) surface as the active component. Usually, the active component, the carrier and the interaction between the two will directly affect the catalytic performance of the carbon dioxide hydrogenation reaction. 2For hydrogenation reactions, the charge separation efficiency of the catalyst also has an important influence on the catalytic reaction. 2 The supported metal Ni catalyst is an efficient photothermal catalyst for the carbon dioxide hydrogenation reaction. Summary of the invention

[0004] In order to improve the above technical problems, the present invention provides a method for preparing a nickel-titanium composite catalyst, the method comprising:

[0005] (1) TiO 2 calcining in the presence of a reducing gas to obtain an intermediate;

[0006] (2) The intermediate of step (1) is mixed with a Ni precursor solution, heated, and calcined in the presence of a reducing gas to prepare the nickel-titanium composite catalyst.

[0007] According to an embodiment of the present invention, in step (1), the TiO 2 The crystal form of TiO can be selected from at least one of anatase, rutile and brookite. Exemplarily, the TiO 2 Anatase TiO 2 .

[0008] Preferably, the TiO 2 Can be selected from hydrophilic TiO 2 , oleophilic TiO 2 At least one of .

[0009] According to an embodiment of the present invention, in step (1), the TiO 2 The average particle size is 5-1000 nm, preferably 5-200 nm, and exemplarily is 5 nm, 20 nm, 25 nm, 40 nm, 60 nm, 80 nm, 100 nm, and 200 nm.

[0010] According to an embodiment of the present invention, in step (1), the reducing gas contains H 2 , and may also contain N 2 At least one of the inert atmosphere gases such as Ar, He, etc. 2 The volume ratio is ≥10%, preferably 20-100%, more preferably 40-100%.

[0011] According to an embodiment of the present invention, in step (1), the flow rate of the reducing gas is 10-100 mL / min, preferably 20-50 mL / min.

[0012] According to an embodiment of the present invention, in step (1), the calcination temperature is 200-700°C, preferably 400-500°C; the calcination time is 1-12h, preferably 2-6h. The heating rate during calcination is 1-10°C / min, preferably 2-5°C / min, for example 3°C / min.

[0013] According to an embodiment of the present invention, in step (2), the Ni precursor is selected from nickel nitrate (Ni(NO 3 ) 2 6H 2 O), nickel chloride (NiCl 2 6H 2 O), nickel acetate (Ni(CH3COO)2), preferably nickel nitrate.

[0014] According to an embodiment of the present invention, in step (2), the reducing gas contains H 2 , and may also contain N 2 At least one of the inert atmosphere gases such as Ar, He, etc. 2 The volume ratio is ≧10%, preferably 20 to 100%, more preferably 40 to 100%.

[0015] According to an embodiment of the present invention, in step (2), the calcination temperature is 200 to 700° C., preferably 400 to 500° C.; the calcination time is 1 to 12 hours, preferably 2 to 6 hours.

[0016] According to an embodiment of the present invention, in step (2), the flow rate of the reducing gas is 10-100 mL / min, preferably 20-50 mL / min; the heating rate during the calcination is 1-10°C / min, preferably 2-5°C / min, for example 3°C / min.

[0017] According to an embodiment of the present invention, in step (2), the Ni precursor solution is prepared by dissolving the Ni precursor in water. In the present invention, the water content is not particularly limited, as long as the raw materials can be dissolved in water.

[0018] According to an embodiment of the present invention, in step (2), the content of Ni in the Ni precursor is TiO 2 2 to 50 wt%, preferably 5 to 30 wt%, more preferably 5 to 20 wt%.

[0019] According to an embodiment of the present invention, in step (2), the heating temperature is 60 to 150° C., preferably 70 to 100° C., and the heating time is 4 to 24 hours, preferably 8 to 20 hours.

[0020] The present invention also provides a nickel-titanium composite catalyst prepared by the above method. The present invention also provides a nickel-titanium composite catalyst in catalyzing CO 2 Application in hydrogenation reactions.

[0021] Preferably, the catalysis is photothermal catalysis; more preferably, the photothermal catalysis is that the nickel-titanium catalyst absorbs light energy of at least one of visible light, infrared light and ultraviolet light, converts the absorbed light energy into heat energy, and then catalyzes CO 2 Hydrogenation reaction.

[0022] Furthermore, the incident light intensity used in the photothermal catalysis can be 0.1-100 W / cm 2 , for example, the incident intensity may be 5.0 W / cm 2 、10.0W / cm 2 、12.0W / cm 2 、13.0W / cm 2 The reaction pressure is normal pressure; H 2 With CO 2 The molar ratio is 0.5 to 6, preferably 2 to 4; the gas volume space velocity is 3000 to 200000 mL g cat -1 h -1 , preferably 50000~150000mLg cat -1 h -1 .

[0023] The present invention changes the carrier TiO in the nickel-titanium composite catalyst 2 The particle size of TiO 2 When the particle size is small (5-30 nm), the carbon-based products of the reaction are highly selective to produce CH 4 ; TiO 2 When the particle size is large (100-200nm), the carbon-based products of the reaction produce CO with high selectivity; when the particle size is between 40 and 60nm, CH 4 and CO, and the product CH 4 The selectivity with CO can be improved by reducing the pretreated TiO 2 The particle size of the catalyst carrier can be effectively regulated. In the catalyst described in the present invention, TiO 2 After the carrier is loaded with the metal Ni active component, it has greatly improved light absorption capacity and photothermal conversion capacity, and the catalyst has good stability.

[0024] Beneficial effects of the present invention:

[0025] The catalyst preparation method provided by the present invention has readily available raw materials, simple process and easy industrialization. 2 The particle size of the carrier can effectively adjust the metal Ni / TiO 2 The interaction between Ni / TiO 2 The photogenerated charge separation efficiency is improved, and the selectivity of the carbon dioxide hydrogenation reaction products is finally adjusted. The catalyst of the present invention can realize photothermal conversion without the need for an external heating device, and the nickel-titanium composite catalyst can achieve strong light absorption under the full spectrum. The catalyst of the present invention converts the absorbed light energy into heat energy, and can achieve efficient CO2 hydrogenation without the need for an external heating device. 2 Hydrogenation conversion: The catalyst of the present invention still maintains high catalytic activity and stability after a long period of catalytic experiment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray diffraction patterns of the catalysts of Examples 1-3 and Comparative Examples 1-3 are shown.

[0027] Figure 2 These are ordinary transmission electron microscope images and high-resolution transmission electron microscope images of the catalysts of Examples 1-3.

[0028] Figure 3 The UV-visible diffuse reflectance spectra of the catalysts of Examples 1-3 and Comparative Examples 1-3 are shown.

[0029] Figure 4 The photoluminescence spectra of the catalysts of Examples 1-3 and Comparative Examples 1-3 are shown.

[0030] Figure 5 This is the hydrogen temperature-programmed reduction spectrum of the catalyst of Example 1-3.

[0031] Figure 6 The electron paramagnetic resonance spectra of the catalysts of Examples 1-3 are shown in FIG.

[0032] Figure 7 The catalysts of Examples 1-3 generate CH 4 , CO rate diagram.

[0033] Figure 8 The catalysts of Examples 1-3 generate CH 4 , CO selectivity diagram.

[0034] Fig. 9 The CH generated in the durability test of Example 1 4 Rate and generation of CH 4 Selectivity diagram and CO generation rate and CO generation selectivity diagram in the durability experiment of Example 3. DETAILED DESCRIPTION

[0035] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0036] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0037] Example 1

[0038] The Ni / TiO 2 The preparation process of the catalyst includes the following steps:

[0039] Step 1: Take 1g of hydrophilic anatase TiO with a particle size of 25nm 2 Place in a tube furnace and flow pure H at 50 mL / min. 2 The temperature was raised to 500°C at a rate of 3°C / min and maintained for 3 hours to obtain the pretreated TiO 2 carrier.

[0040] Step 2: Take 500 mg of the treated TiO 2 , dispersed in 100 mL of water, ultrasonically stirred for 10 min; 2.15 mL of 116.2 mg / mL Ni(NO) 3 6H 2 O was added to the above solution, and the mixture was heated and stirred at 90 °C until the solvent was evaporated. The obtained solid was dried in an oven at 100 °C for 6 h, and then heated in 50 mL / min of pure H 2 The temperature was raised to 450℃ at a rate of 3℃ / min and maintained for 3 hours to obtain Ni-TiO 2 -25. After the ICP test of the catalyst of this example, it was found that the actual loading amount of Ni was 9.0wt% (i.e. Ni:TiO 2 The mass ratio is 9.0wt%).

[0041] Example 2

[0042] Step 1: Take 1g of hydrophilic anatase TiO with a particle size of 60nm 2 Place in a tube furnace and flow pure H at 50 mL / min. 2 The temperature was raised to 500°C at a rate of 3°C / min and maintained for 3 hours to obtain the pretreated TiO 2 carrier.

[0043] Step 2: Take 500 mg of the treated TiO 2, dispersed in 100 mL of water, ultrasonically stirred for 10 min; 2.15 mL of 116.2 mg / mL Ni(NO) 3 6H 2 O was added to the above solution, and the mixture was heated and stirred at 90 °C until the solvent was evaporated. The obtained solid was dried in an oven at 100 °C for 6 h, and then heated in 50 mL / min of pure H 2 The temperature was raised to 450℃ at a rate of 3℃ / min and maintained for 3 hours to obtain Ni-TiO 2 -60 After the ICP test of the catalyst of this example, it was found that the actual loading amount of Ni was 9.3wt% (i.e., Ni:TiO 2 The mass ratio is 9.3wt%).

[0044] Example 3

[0045] Step 1: Take 1g of hydrophilic anatase TiO with a particle size of 100nm 2 Place in a tube furnace and flow pure H at 50 mL / min. 2 The temperature was raised to 500°C at a rate of 3°C / min and maintained for 3 hours to obtain the pretreated TiO 2 carrier.

[0046] Step 2: Take 500 mg of the treated TiO 2 , dispersed in 100 mL of water, ultrasonically stirred for 10 min; 2.15 mL of 116.2 mg / mL Ni(NO) 3 6H 2 O was added to the above solution, and the mixture was heated and stirred at 90 °C until the solvent was evaporated. The obtained solid was dried in an oven at 100 °C for 6 h, and then heated in 50 mL / min of pure H 2 The temperature was raised to 450℃ at a rate of 3℃ / min and maintained for 3 hours to obtain Ni-TiO 2 -100. After the ICP test of the catalyst of this example, it was found that the actual loading amount of Ni was 9.5wt% (i.e. Ni:TiO 2 The mass ratio is 9.5wt%).

[0047] Comparative Example 1

[0048] Take 1g of hydrophilic anatase TiO with a particle size of 25nm 2 Place in a tube furnace and flow pure H at 50 mL / min. 2 The temperature was raised to 500°C at a rate of 3°C / min and maintained for 3 hours to obtain the pretreated TiO 2 -25.

[0049] Comparative Example 2

[0050] Take 1g of hydrophilic anatase TiO with a particle size of 60nm 2 Place in a tube furnace and flow pure H at 50 mL / min. 2 The temperature was raised to 500°C at a rate of 3°C / min and maintained for 3 hours to obtain the pretreated TiO 2 -60.

[0051] Comparative Example 3

[0052] Take 1g of hydrophilic anatase TiO with a particle size of 100nm 2 Place in a tube furnace and flow pure H at 50 mL / min. 2 The temperature was raised to 500°C at a rate of 3°C / min and maintained for 3 hours to obtain the pretreated TiO 2 -100.

[0053] Catalytic performance test

[0054] The catalyst activity was evaluated under dynamic conditions (by testing the CO 2 To CH 4 The reactor used was a 40 mL stainless steel static reactor. Before the experiment, 10 mg of each catalyst prepared in Examples 1-3 was weighed as a sample and placed in the reactor, and CO was introduced into the reactor. 2 , H 2 After 30 minutes of heating, the reaction was carried out using a 300W Perfil xenon lamp. The product CH 4 and CO were detected by gas chromatography, among which CH 4 The generation rate and CO generation rate are respectively expressed by the following formulas (1) and (2):

[0055] CH 4 Production rate (mmol / g cat ·h) = [CH 4 ] / (catalyst mass*reaction time) (1)

[0056] CO production rate (mmol / g cat h) = [CO] / (catalyst mass * reaction time) (2)

[0057] Among them, the [CH 4 ] and [CO] are both molar concentrations.

[0058] Figure 1The X-ray diffraction patterns of the catalysts of Examples 1-3 and Comparative Examples 1-3 show that Ni is present in the TiO 2 All samples of TiO 2 The phases are all anatase type.

[0059] Figure 2 The conventional transmission electron microscopy images and high-resolution transmission electron microscopy images of the catalysts of Examples 1-3 are shown. 2 The average size of TiO is 25 nm; in Example 2, 2 The size of TiO is 60nm; in Example 3, 2 The size of the Ni particles is 100 nm; Examples 1-3 have Ni particles loaded on TiO 2 surface.

[0060] Figure 3 The UV-visible diffuse reflectance spectra of the catalysts of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1. Ni doping greatly improves the light absorption capacity of the material, and the order of light absorption capacity is Ni / TiO 2 -25>Ni / TiO 2 -60>Ni / TiO 2 -100>TiO 2 -25>TiO 2 -60>TiO 2 -100, indicating that in the catalyst prepared by this patent, the smaller the carrier particle size, the stronger the light absorption ability.

[0061] Figure 4 The photoluminescence spectra of the catalysts of Examples 1-3 and Comparative Examples 1-3 show that the order of charge separation efficiency is Ni / TiO 2 -25>Ni / TiO 2 -60>Ni / TiO 2 -100>TiO 2 -25>TiO 2 -60>TiO 2 -100, indicating that in the catalyst prepared by this patent, the smaller the carrier particle size, the stronger the charge separation efficiency.

[0062] Figure 5 The hydrogen temperature-programmed reduction spectrum of the catalyst of Example 1-3 is shown in FIG. Figure 5 It can be seen that the Ni-Ti interaction strength in the catalysts prepared in Examples 1-3 is Ni / TiO 2 -25>Ni / TiO 2 -60>Ni / TiO 2 -100, indicating that in the catalyst prepared in this patent, the smaller the carrier particle size, the stronger the interaction strength between the metal and the carrier.

[0063] Figure 6 is the electron paramagnetic resonance spectrum of the catalyst of Example 1-3, from Figure 6 It can be seen that under dark conditions, the oxygen vacancy intensity in the catalysts prepared in Examples 1-3 is Ni / TiO 2 -25>Ni / TiO 2 -60>Ni / TiO 2 -100, indicating that in the catalyst prepared by the present invention, the smaller the carrier particle size, the more oxygen vacancies are generated on the surface, and under light conditions, oxygen vacancy signals and Ti 3+ The signal is enhanced, and the degree of enhancement conforms to the following rules: Ni / TiO 2 -25>Ni / TiO 2 -60>Ni / TiO 2 -100, which may be closely related to its photogenerated charge separation efficiency.

[0064] Figure 7 The catalysts of Examples 1-3 generate CH 4 , CO rate diagram. In Example 1, TiO 2 The prepared material Ni / TiO with a particle size of 25nm 2 -25 has a strong CH 4 Generation rate; CH 4 The generation rate is Ni / TiO 2 -25>Ni / TiO 2 -60>Ni / TiO 2 -100, CO generation rate is Ni / TiO 2 -25 <Ni / TiO 2 -60 <Ni / TiO 2 -100, indicating that in the catalyst prepared in this patent, the smaller the carrier particle size, the more favorable it is for generating CH 4 .

[0065] Figure 8 The catalysts of Examples 1-3 generate CH 4 , CO selectivity diagram. In Example 1, TiO 2 The prepared material Ni / TiO with a particle size of 25nm 2 -25 has close to 95% of CH 4 Selectivity; and by adjusting the particle size of the carrier in the catalyst of the present invention, the reaction selectivity can be further regulated. In Example 2, TiO 2 The prepared material Ni / TiO with a particle size of 60nm 2 -60 pairs of CH 4The selectivity decreases when the carrier particle size is increased to 100 nm, that is, when the TiO 2 The prepared material Ni / TiO with a particle size of 100 nm 2 -100 has a strong CO generation rate and a CO selectivity close to 95%.

[0066] Fig. 9 The CH generated in the durability test of Example 1 4 Rate and generation of CH 4 The selectivity diagram and the CO generation rate and CO generation selectivity diagram of Example 3 in the durability test. It can be shown that the Ni / TiO 2 -25 has good and stable methane yield and excellent selectivity, Ni / TiO 2 -25 has good and stable CO yield and excellent selectivity. The two catalysts can meet different product requirements and be put into practical application.

[0067] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nickel-titanium composite catalyst, characterized in that: The method comprises: (1) calcining TiO2 in the presence of a reducing gas to obtain an intermediate; (2) The intermediate of step (1) is mixed with a Ni precursor solution, heated, and calcined in the presence of a reducing gas to prepare the nickel-titanium composite catalyst.

2. The method according to claim 1, characterized in that In step (1), the crystal form of TiO2 is selected from at least one of anatase, rutile and brookite. Preferably, in step (1), the average particle size of TiO2 is 5-1000nm, preferably 5-200nm.

3. The method according to claim 1 or 2, characterized in that: In step (1), the reducing gas contains H2 and at least one of the inert atmosphere gases N2, Ar, and He, wherein the volume proportion of H2 is ≥10%. Preferably, in step (1), the flow rate of the reducing gas is 10-100 mL / min; In step (1), the calcination temperature is 200-700°C; the calcination time is 1-12h, and the heating rate during calcination is 1-10°C / min.

4. The method according to any one of claims 1 to 3, characterized in that: In step (2), the Ni precursor is selected from at least one of nickel nitrate, nickel chloride and nickel acetate. Preferably, in step (2), the reducing gas contains H2 and at least one of the inert atmosphere gases N2, Ar, and He, wherein the volume proportion of H2 is ≧10%, preferably 20-100%, and more preferably 40-100%.

5. The method according to any one of claims 1 to 4, characterized in that: In step (2), the calcination temperature is 200 to 700° C., and the calcination time is 1 to 12 hours.

6. The method according to any one of claims 1 to 5, characterized in that: In step (2), the flow rate of the reducing gas is 10-100 mL / min, and the heating rate during the calcination is 1-10° C. / min.

7. The method according to any one of claims 1 to 6, characterized in that: In step (2), the Ni precursor solution is prepared by dissolving the Ni precursor in water. Preferably, in step (2), the Ni content in the Ni precursor is 2 to 50 wt % of TiO2. Preferably, in step (2), the heating temperature is 60 to 150° C., and the heating time is 4 to 24 hours.

8. A nickel-titanium composite catalyst prepared by the method according to any one of claims 1 to 7.

9. Use of the nickel-titanium composite catalyst according to claim 18 in catalyzing CO2 hydrogenation reaction.

10. The use according to claim 9, characterized in that: The catalysis is photothermal catalysis; preferably, the photothermal catalysis is to absorb the light energy of at least one of visible light, infrared light and ultraviolet light through the nickel-titanium catalyst, convert the absorbed light energy into heat energy, and then catalyze the CO2 hydrogenation reaction. Preferably, the incident light intensity used in the photothermal catalysis can be 0.1-100 W / cm 2 The reaction pressure is normal pressure; the molar ratio of H2 to CO2 in the raw gas is 0.5-6, and the gas volume space velocity is 3000-200000mLg cat -1 h -1 .

Citation Information

Cited By

  • Preparation method and application of Ni / TiO2 nanorod catalyst

    CN120861056A